Asymptotic analysis of a doubly nonlinear diffusion equation - King, John R. (Elsevier, 2016)
We investigate the doubly nonlinear diffusion equation ∂u/∂t=1/n ∇.(u^m│∇u│^n-1) ∇u) and the same equation expressed in terms of a `pressure' variable. We classify various classes of compacted supported solutions, as well as finite-mass solutions that decay algebraically at infinity. A number of novel phenomena are identified, particularly for n<0, that seem to us worthy of further mathematical investigation.